HAMBATAN KAMAR DAGANG DAN INDUSTRI (KADIN) KOTA DUMAI DALAM MENINGKATKAN KERJASAMA PERDAGANGAN ANTARA INDONESIA DAN MALAYSIA - Arief, Muhammad; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Chamber of Commerce and Industry (Kadin) of Kota Dumai plays a strategic role in facilitating trade cooperation between Indonesia and Malaysia, particularly within the framework of complex interdependence, which reflects the economic interconnection between the two countries. This study aims to identify the obstacles faced by Kadin Dumai in enhancing bilateral trade relations and to analyze the strategies that can be implemented to overcome these challenges. Using a qualitative descriptive approach, this research examines trade regulations, bureaucratic factors, and infrastructure limitations that affect Kadin Dumai’s effectiveness in the dynamics of regional trade interdependence. The findings indicate that the main barriers include complex cross-border trade regulations, inefficient bureaucratic processes, and inadequate logistical infrastructure in Dumai City. Furthermore, asymmetric market information and the limited involvement of the private sector in trade policy formulation further complicate the complex interdependence between business actors in both countries. To address these challenges, strategies such as strengthening coordination between Kadin Dumai and central and regional governments, enhancing economic diplomacy through bilateral forums, and optimizing trade missions and exhibitions as instruments to strengthen cross-border economic connectivity are essential. Keywords: Kadin Dumai, complex interdependence, trade cooperation, trade barriers, bilateral relations, trade mission, trade exhibition.